2006
DOI: 10.1039/b517886j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient preparation and improved sensitivity of molecularly imprinted polymers using room temperature ionic liquids

Abstract: Synthesis of trans-aconitic acid molecularly imprinted polymers in [bmim][BF4] and [bmim][PF6] under photochemical (5 degrees C, AIBN) and thermal (60 degrees C, AIBN) conditions gave polymer micro-spheres (<200 nm), under bulk and precipitation polymerisation conditions, and higher selectivity indices (100% improvement) relative to the more traditional precipitation polymerisation (CH3CN, high solvent volumes) approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 18 publications
3
59
0
Order By: Relevance
“…These results provide a good foundation for the current study (Booker et al 2007). Previous research conducted by our group indicated that a change in the anion of the RTIL used as polymerisation solvent (from BF 4 -to PF 6 -) influences polymer selectivity for the template for both trans-aconitic acid and cocaineimprinted polymers (Booker et al, 2005(Booker et al, , 2006(Booker et al, , 2008 (Booker et al 2006(Booker et al , 2007Wang et al 2006Wang et al , 2008He et al 2008). The work reported herein aims to identify RTILs that reproducibly create well-performing MIPs, and assess factors contributing to variations in polymer performance.…”
Section: Scope Of This Studymentioning
confidence: 52%
See 4 more Smart Citations
“…These results provide a good foundation for the current study (Booker et al 2007). Previous research conducted by our group indicated that a change in the anion of the RTIL used as polymerisation solvent (from BF 4 -to PF 6 -) influences polymer selectivity for the template for both trans-aconitic acid and cocaineimprinted polymers (Booker et al, 2005(Booker et al, , 2006(Booker et al, , 2008 (Booker et al 2006(Booker et al , 2007Wang et al 2006Wang et al , 2008He et al 2008). The work reported herein aims to identify RTILs that reproducibly create well-performing MIPs, and assess factors contributing to variations in polymer performance.…”
Section: Scope Of This Studymentioning
confidence: 52%
“…This results from later phase separation of the growing polymer chains, resulting in a lower degree of aggregation of the polymer particles. Generally, RTIL prepared MIPs and NIPs have been observed to swell less (Booker et al, 2006). It is important to note here though, that the absence of polymer swelling does not preclude the development of high specificity, high capacity MIPs.…”
Section: Mip Swellingmentioning
confidence: 91%
See 3 more Smart Citations